PENGARUH SUHU DAN LAMA PROSES MENGGORENG (DEEP FRYING) TERHADAP PEMBENTUKAN ASAM LEMAK TRANS - Sartika, Ratu Ayu Dewi (Makara Journal of Science, 2009)
Influencing of Deep Frying in Forming of Trans Fatty Acid. Frying process is one of the cooking’s techniques using vegetable oil. This process is commonly used in food industry, restaurants, food services, food retail and household scale. This is a laboratory experimental study which performed in laboratory of Public Health Nutrition FKM-UI and Integrated Laboratory IPB, Bogor from December 2005 until March 2006. It was conducted by two (2) type of treatment (used cooking oil ex cassava and meat) with 4 (four) times for each treatment. The objective of this study is to know the influence of frying by using deep frying (frying in high temperature and in a long time) and repeating to trans fatty acid formation in cooking oil. From the result revealed that fatty acid type mostly contained in a fresh cooking oil is oleic acid. Trans fatty acid was formed after second repeating of deep frying and increased in line with the frequent of repeating. Correlation test result had shown that negative association between elaidic acid (trans) and oleic acid (cis) (r = - 0,8; p value = 0.016). In accordance with the beginning of trans fatty acid formation, it would be better to use the cooking oil not more than twice.